Does OTC derivatives reform incentivize central clearing? - Ghamami, Samim; Glasserman, Paul (Journal of Financial Intermediation, 2017)
Regulatory changes in the over-the-counter (OTC) derivatives market seek to reduce systemic risk. The reforms require that standardized derivatives be cleared through central counterparties (CCPs), and they set higher capital and margin requirements for non-centrally cleared derivatives. We investigate whether these requirements create a cost incentive in favor of central clearing, as intended. We compare the total capital and collateral costs when banks transact fully bilaterally and when they clear all contracts through CCPs. We calibrate our model using data on the OTC market collected by the Federal Reserve. We find that the cost incentive may not favor central clearing. The main factors driving the cost comparison are netting benefits, the margin period of risk, and CCP guarantee fund requirements. Lower guarantee fund requirements lower the cost of clearing but make CCPs less resilient.